Precipitation variability and soil water content in Pampean Flatlands (Argentina) - Forte Lay, J. (2008)
The goal of this paper is to show the precipitation variability in pampean flatlands during the last decades and the con sequential changes in soil water content. Two periods of 30 years each (1947-1976 and 1977-2006) were analyzed and an increase in annual precipitation all over the region was found in the last one. Areas with different increase in precipitation were located and these varied between 50 and 200 mm in annual precipitation. The bigger increase was found in the warm semester (October-March) in the center-western part of the region. One of the consequences of this was the increase in soil water supplies, which is very important for the development of agricultural activities.